THE FINANCIAL DEFICIT OF PENSION FUND DURING COVID-19 PANDEMIC AND THE STRATEGY OF DIVERSIFYING AND ACCOUNTING FOR INVESTED ASSETS ACCORDING TO INTERNATIONAL PUBLIC SECTOR ACCOUNTING STANDARDS (World Economics and Finance Bulletin, 2022)
The research aims to study and analyze the conceptual aspects of retirement funds. Specifically, the most crucial challenges pension funds face during the Covid-19 pandemic. Additionally, studying the importance of diversifying the investments of the pension fund assets and accounting for them based on the application of international public sector accounting standards. The study begins by investigating the problem of diversification lack of the assets invested in the retirement fund that leads to the emergence of a financial deficit in funding during the covid-19 pandemic. Consequently, it leads to the retirement fund’s inability to fulfill its obligations towards the beneficiaries in the future. According to a checklist, a survey is conducted for the most important pension funds in various countries whose investments were affected with/without the Covid-19 pandemic. The strategy of diversifying assets invested in pension funds in countries of the world was revealed according to another checklist. Therefore, the scholars are motivated to propose designing financial statements for the Iraqi pension fund according to international public sector accounting standards. The design does not prepare these lists and is not entrusted with diversifying its investments and Financial disclosure in the Balance Sheet and Income and Cash Flow Statement.